Characteristics of self-concept of computer gamers - Galina Chaika (Social Welfare: Interdisciplinary Approach)
Computer games, having become widespread, are a powerful cultural factor of present days that affects various aspects of a player’s personality. This article discusses such influence on user’s self-concept. The self-concept peculiarities of people who overindulge in computer games are highlighted. Interrelation between favorite game genres, chosen by players, and changes in their self-concept is revealed.